Active Learning as an Effective Tool to Enhance Cognition - J.M., Smitha (JOURNAL OF INDIAN EDUCATION, 2017)
Children need to be encouraged to explore alternative thinking, multiple view and creative insights. The capacity for abstract thinking begins around the age eleven. At this stage, of adolescents reason much like a scientist searching for solutions in the laboratory. They come up with new, more general logical rules through internal reflection. So, the teaching methodology used should be designed in such a way that it satisfies the cognitive need of the adolescents. The highest value that all methods should try to inculcate is love to work and desire to do it with the highest measure of efficiency of which one is capable of. Research indicates that active involvement is an additional characteristic that increases student’s interest in an activity. An attempt has been made through this article to give an insight regarding the significance of active learning strategies in enhancing the information processing activities of human brain.